Diversification and collapse of a telomere elongation mechanism - Saint-Leandre, Bastien; Nguyen, Son C.; Levine, Mia T. (Genome Research, 2019)
In most eukaryotes, telomerase counteracts chromosome erosion by adding repetitive sequence to terminal ends. Drosophila melanogaster instead relies on specialized retrotransposons that insert exclusively at telomeres. This exchange of goods between host and mobile element—wherein the mobile element provides an essential genome service and the host provides a hospitable niche for mobile element propagation—has been called a “genomic symbiosis.” However, these telomere-specialized, jockey family retrotransposons may actually evolve to “selfishly” overreplicate in the genomes that they ostensibly serve. Under this model, we expect rapid diversification of telomere-specialized retrotransposon lineages and, possibly, the breakdown of this ostensibly symbiotic relationship. Here we report data consistent with both predictions. Searching the raw reads of the 15-Myr-old melanogaster species group, we generated de novo jockey retrotransposon consensus sequences and used phylogenetic tree-building to delineate four distinct telomere-associated lineages. Recurrent gains, losses, and replacements account for this retrotransposon lineage diversity. In Drosophila biarmipes, telomere-specialized elements have disappeared completely. De novo assembly of long reads and cytogenetics confirmed this species-specific collapse of retrotransposon-dependent telomere elongation. Instead, telomere-restricted satellite DNA and DNA transposon fragments occupy its terminal ends. We infer that D. biarmipes relies instead on a recombination-based mechanism conserved from yeast to flies to humans. Telomeric retrotransposon diversification and disappearance suggest that persistently “selfish” machinery shapes telomere elongation across Drosophila rather than completely domesticated, symbiotic mobile elements.
10.1101/gr.245001.118